2013
DOI: 10.1016/j.giq.2013.05.015
|View full text |Cite
|
Sign up to set email alerts
|

A framework for interpreting social media interactions in the public sector

Abstract: a b s t r a c t Keywords:Social media measurement Digital interactions Open Government Initiative U.S. federal government Social media applications are extending the information and communication technology landscape in the public sector and are used to increase government transparency, participation and collaboration in the U.S. federal government. The success, impact and performance of these new forms of bi directional and networked interactions can provide insights to understand compliance with the mandate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
390
2
49

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 401 publications
(450 citation statements)
references
References 26 publications
9
390
2
49
Order By: Relevance
“…A pesquisa se justifica, pois, no cenário político atual, faz-se necessário entender o uso de aplicativos de mídia social como canais aceitáveis para as interações entre governo e seus diversos públicos que podem, potencialmente, fazer a diferença nas percepções e sentimentos dos cidadãos em relação ao governo (MERGEL, 2013). Apesar da crescente atenção à análise de conteúdo gerado pelos usuários das mídias sociais, "os pesquisadores têm pouco conhecimento sobre como aplicar os métodos de mineração de conteúdo" (YOON;ELHADAD;BAKKEN, 2013, p. 122), faltando métri-cas adequadas que identifiquem, nessas mídias, os impactos das ações dos governos (MERGEL, 2013;HOFMANN et al, 2013).…”
Section: Daniel José Silva Oliveira and Paulo Henrique De Souza Bermejounclassified
See 2 more Smart Citations
“…A pesquisa se justifica, pois, no cenário político atual, faz-se necessário entender o uso de aplicativos de mídia social como canais aceitáveis para as interações entre governo e seus diversos públicos que podem, potencialmente, fazer a diferença nas percepções e sentimentos dos cidadãos em relação ao governo (MERGEL, 2013). Apesar da crescente atenção à análise de conteúdo gerado pelos usuários das mídias sociais, "os pesquisadores têm pouco conhecimento sobre como aplicar os métodos de mineração de conteúdo" (YOON;ELHADAD;BAKKEN, 2013, p. 122), faltando métri-cas adequadas que identifiquem, nessas mídias, os impactos das ações dos governos (MERGEL, 2013;HOFMANN et al, 2013).…”
Section: Daniel José Silva Oliveira and Paulo Henrique De Souza Bermejounclassified
“…Apesar da crescente atenção à análise de conteúdo gerado pelos usuários das mídias sociais, "os pesquisadores têm pouco conhecimento sobre como aplicar os métodos de mineração de conteúdo" (YOON;ELHADAD;BAKKEN, 2013, p. 122), faltando métri-cas adequadas que identifiquem, nessas mídias, os impactos das ações dos governos (MERGEL, 2013;HOFMANN et al, 2013).…”
Section: Daniel José Silva Oliveira and Paulo Henrique De Souza Bermejounclassified
See 1 more Smart Citation
“…The networking approach emphasizes a dialogue whereas engagement invites co-production of content without necessarily engaging contributors in dialogue (Mossberger et al, 2013: 353). However, research has shown that local governments predominantly stick to representation, applying 'push strategies' to provide one-way information (Mergel, 2013a(Mergel, , 2013b. According to Buccoliero and Bellio (2010: 236), there is a substantial immaturity of web strategies which are modulated on structures and organizational responsibilities instead of on the needs of citizens' empowerment.…”
Section: Public Participation and The Turn To Technologymentioning
confidence: 99%
“…In characterizing the presence of federal agencies on social networks as one of the tools of openness, we should note that the extent to which this tool has been implemented at federal executive agencies varies signifi cantly, although on the whole it is still at a fairly low level -based on Mergel (2013), at the level of providing information.…”
Section: Th E Presence Of Federal Executive Agencies In Social Networkmentioning
confidence: 99%